Praktik Sewa Menyewa Lapangan Bulu Tangkis - Nasution, Rahmad Faisal (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study discusses the Compilation Review of Sharia Economic Law on the Practice of Leasing Badminton Fields in Tano Bato Village, North Padangsidimpuan District, Padangsidimpuan City. This research is motivated by the use of rented goods that are not in accordance with the provisions of Sharia Economic Law (KHES) due to the tenant misusing the rented goods into provisions that have been prohibited according to Islamic Shari'a. The formulation of the problem in this study is how the practice of renting badminton courts in Tano Bato Village, North Padangsidimpuan District, Padangsidimpuan City and how the Compilation Review of Sharia Economic Law on the practice of renting badminton courts in Tano Bato Village, North Padangsidimpuan District, Padangsidimpuan City. Based on the formulation of the problem, the purpose of this study is to find out the practice of renting badminton courts in Tano Bato Village, North Padangsidimpuan District, Padangsidimpuan City and to find out how the Sharia Economic Law Compilation reviews the practice of renting badminton courts in Tano Bato Village, North Padangsidimpuan District. Padangsidimpuan City. This study uses qualitative research that seeks to describe, describe a situation and event based on the facts that occur in the field to obtain conclusions. As for the subject in this study, the tenants use the rented goods to the road which is clearly contrary to the provisions of KHES in article 274 paragraph 2. Then the data collection technique in this study uses snowball sampling technique by using interviews, observations to field tenants and owners. badminton court in Tano Bato Village. The results of this study indicate that the practice of leasing badminton courts in Tano Bato Village is not in accordance with the provisions of the Sharia Economic Law Compilation in article 274 paragraph 2 because the tenant has used goods into immoral ways or gambling, which in essence the practice is not allowed according to the Shari'a. Islam and the provisions of the Sharia Economic Law Compilation.